Integrated Assessment of the Proliferation of Small Dams and Erosion Susceptibility: The Ivaí River Watershed, Southern Brazil - Tondati, Mariana Manrique; Morais, Eduardo Souza de (Sociedade & Natureza, 2025)
The proliferation of small dams in watersheds has raised growing concerns about their potential impacts on the connectivity of fluvial systems, particularly regarding sediment transport, flow variability, and the integrity of aquatic habitats. In this context, this study investigated the distribution of hydroelectric dams and the erosion susceptibility, using the Ivaí River Watershed, Paraná state, Brazil, as a case study to assess geomorphological implications at the watershed scale. The Ivaí River is the largest free-flowing river in Southern Brazil, and also stands out as the main unregulated tributary of the Paraná River, granting it a strategic role in maintaining the hydro-sedimentological and ecological integrity of the Upper Paraná River watershed. The analyses in the Ivaí River Watershed were conducted using cadastral data from hydroelectric projects and geoprocessing techniques based on map algebra. A total of 21 projects, either operational or approved for construction, were identified. Their drainage areas represent 13.7% of the watershed, mostly concentrated in the upper course, characterised by dissected relief, the presence of Neosols, and high rainfall indices. Currently, its main course remains free-flowing; however, studies for future projects threaten the river integrity. The overlap between areas of high geomorphological vunerability and project concentration indicates potential cumulative risks to fluvial dynamics. The results show that even smaller-scale dams, when located in sensitive areas, can disrupt fluvial connectivity and morphodynamic processes with cumulative effects. This scenario highlights the need for territorial planning policies that integrate the conservation of fluvial systems essential to maintaining ecosystem services in their decision-making.